Contamination effects on sexual selection in wild dung beetles. (1st June 2022) - Villada‐Bedoya, Sebastián; Córdoba‐Aguilar, Alex; Escobar, Federico; González‐Tokman, Daniel
Abstract: Sexual selection influences the expression of secondary sexual traits, which are costly to produce and maintain and are thus considered honest indicators of individual condition. Therefore, sexual selection could select for high‐quality individuals able to respond to stressful conditions, with impacts on population‐level fitness. We sampled dung beetles from 19 pastures and investigated if contamination by herbicides and veterinary drugs modifies male investment in sexually selected traits and has associated population‐level effects. We measured horn size, condition dependence (i.e. size‐corrected body mass) and allometry, besides abundance and sexual size dimorphism in three species: Copris incertus, Euoniticellus intermedius and Digitonthophagus gazella . In contrary to our expectations, horn size was independent of contamination and individual condition. However, strong positive allometric relationships were reduced by herbicide contamination for C . incertus and D . gazella and were increased by ivermectin for C . incertus, revealing differential investment in horn production according to body size in contaminated habitats. At the population level, large‐horned C. incertus males were more abundant in contaminated pastures, potentially revealing a case of evolutionary rescue by sexual selection or a plastic response to higher population densities. Finally, chemical compounds affected the sexual size dimorphism of all three species, with potential effects on female fecundity or intrasexual selection. Together, our findings indicate that contamination interferes with sexual selection processes in the wild, opening new questions regarding the role of sexual selection in favouring species persistence in contaminated environments. Abstract : By evaluating horned dung beetles in contaminated cattle pastures, our study reveals that contamination interferes with sexual selection by affecting male's relative investment to sexual traits. Higher abundance of large‐horned males in contaminated pastures indicates demographic impacts of sexual selection in nature and can be explained by evolutionary rescue promoted by sexual selection or by plastic responses in horn size according to population density. The orange arrows support the results of this work.